Opioid Overdose, Naloxone Administration, and Survival Outcomes in Puerto Rico: A Retrospective Analysis, 2019–2023 - Garcia, German H.; Nacer, Samir A.; Zanko, Nikita; Valentin- Meléndez, Keylianis; Tremblay, Raymond L.; Burgos-Barreto, Grisel (Puerto Rico Health Sciences Journal, 2025)
Objective: Puerto Rico has had an alarming increase in opioid distribution, overdose, and opioid-related deaths in the last 2 decades. It is crucial to analyze both the effects of naloxone on mortality in opioidoverdose cases and the current trends in naloxone administration to implement strategies to reduce deaths from opioid-related overdoses. Methods: This retrospective study analyzed opioid overdoses and naloxone administration in Puerto Rico from 2019 to 2023. The data was obtained from the Puerto Rico Mental Health and Anti-Addiction Services Administration and included findings on the spatial and temporal patterns of naloxone administration and a demographic description of the affected populations. Additionally, the study provided an overview of naloxone’s role in fatality reduction in cases of opioid overdose. Results: The key findings indicate a higher prevalence of naloxone administration in public spaces, with peaks occurring during afternoon hours; middle-aged men were the predominant group experiencing opioid overdoses. Additionally, the results demonstrated significantly higher mortality among individuals who did not receive naloxone. Those who received a single dose had a survival rate of 76%, compared to 56% for those who received no naloxone. Furthermore, individuals who received multiple doses of naloxone had an even higher probability of survival. Conclusions: The findings present an effective approach to enhance the targeted geographic distribution of naloxone. Our findings indicated that increasing access to naloxone and strengthening overall community engagement could contribute to mitigating the ongoing public health crisis in Puerto Rico.